2015
DOI: 10.1186/s12889-015-1925-9
|View full text |Cite
|
Sign up to set email alerts
|

What are the main sources of smoking cessation support used by adolescent smokers in England? A cross-sectional study

Abstract: BackgroundAdolescent smoking is a worldwide public health concern. Whilst various support measures are available to help young smokers quit, their utilization of cessation support remains unknown.MethodsA cross-sectional study was conducted using data from the 2012 Smoking, Drinking and Drug Use among Young People survey to quantify the use of seven different types of cessation support by adolescents aged 11-16 in England who reported current smoking and having tried to quit, or ex-smoking. Logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In a previous study, it has been reported that the smoking behavior of friends or parents had a negative effect on the intention or success of smoking cessation (Haas & Schaefer, ). In a study that reported the parental and peer factors associated with smoking in adolescents (Kwak, ), the most significant influential factor on smoking behavior of adolescents was “the number of smoking friends.” In addition, not spending time with friends who smoke was one of the most commonly used methods for successful smoking cessation among adolescents (Shaikh, Nugawela, & Szatkowski, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it has been reported that the smoking behavior of friends or parents had a negative effect on the intention or success of smoking cessation (Haas & Schaefer, ). In a study that reported the parental and peer factors associated with smoking in adolescents (Kwak, ), the most significant influential factor on smoking behavior of adolescents was “the number of smoking friends.” In addition, not spending time with friends who smoke was one of the most commonly used methods for successful smoking cessation among adolescents (Shaikh, Nugawela, & Szatkowski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Parental attachment, an interpersonal factor, was also found to be associated with smoking [ 26 , 27 ]. Parental attachment predicted problem behaviors in adolescents [ 28 ]. A study on the common factors between smoking and delinquency also found that parenting behavior (i.e., emotional bonding between parents and children) was the most potent predictor of smoking in adolescents.…”
Section: Discussionmentioning
confidence: 99%